Dějiny dvou sibiřských „metropolí" - Brzáková, Pavlína (Lidé města, 2002)
Within seven middle-term stays in the Evenck autonomous circle author had a chance to monitor how the political system affects two central settlements and small locations and nomadic groups as well. Their lifestyle resisted in past two years the growing process of assimilation only with major problems. The conflict of two different cultures strengthened by a several immigration waves influenced al! spheres of life of these people. The loss of identity of the nomads who were forced by socialist government to settle down has made some of them to realize that it is necessary to preserve their culture for next generations. This paper is trying to analyze their attempt to resurrect the spirit of the Evenck people.